Soil organic matter decomposition as a key driver of pharmaceutical retention - Lili Szabó; Zoltán Szalai; Attila Csaba Kondor; Anna Vancsik; Balázs Vajna; Csaba László Maller; Csilla Király; Zoltán Dévény; Bruna Silva; Colin A. Booth; László Bauer (Journal of Environmental Management, 2025)

Denoise Extreme learning Machine (DELM) for occupancy estimation in higher education spaces based on CO2 levels - Zhuoqun Sun; Francisco Sierra; Colin A. Booth; Weiyong Si (Energy and Buildings, 2025)

Viability of calcinated wastepaper sludge ash geopolymer in the treatment of road pavement subgrade materials - Jeremiah J. Jeremiah; Samuel J. Abbey; Colin A. Booth; Eyo U. Eyo (Transportation Geotechnics, 2024)

Criteria for Preliminary Risk Assessment of Brownfield Site: An International Survey of Experts - Charf Mahammedi; Lamine Mahdjoubi; Colin Booth; Russell Bowman; Talib E. Butt (Environmental Management, 2022)
Comprehensive risk assessment of brownfield sites requires a broad range of knowledge and multi-disciplinary expertise. Whilst the identification of criteria requirements for preliminary risk assessment has received some attention, there appears to be no studies that have specifically examined professional perspectives relating to these requirements. Yet, variations in professional practitioners’ assessments may have significant consequences for the assessment of risks, and how the criteria are imparted to stakeholders. This study aims to identify the criteria requirements for preliminary risk assessment, using the pollutant linkage model (Source–Pathway–Receptor), and explores cross-disciplinary professional perspectives related to these requirements. To this end, this study commenced with a systematic review to identify various criteria streams required for the preliminary risk assessment of brownfield sites. Thereafter, a questionnaire survey was design and shared with brownfield site professionals. Quantitative analysis of the survey responses ( n = 76) reveals disciplines have markedly different priorities relating to the same hazard. For instance, geophysicists, geochemists, and hydrologists do not raise concerns regarding ground movement that can result from the removal of storage and tanks, whilst the same hazard was considered as having a high importance by other professions (such as geologists and geotechnical engineers). This example, amongst others revealed in the study, underpins potential issues and implications for various stakeholders compiling and/or using preliminary risk assessment criteria. This study clarifies both the key criteria requirements for the preliminary risk assessment of brownfield sites, as well as the importance of recognising how variation in professionals’ perceptions plays in the risk assessment process. Although, specialist knowledge is essential for brownfield site investigation, so is the maintaining a broad-based view of other experts coming from different backgrounds, as this renders holistic risk assessment insights.

Environmental management systems in the architectural, engineering and construction sectors: a roadmap to aid the delivery of the sustainable development goals - Rosemary Horry; Colin A. Booth; Abdul–Majeed Mahamadu; Patrick Manu; Panos Georgakis (Environment, Development and Sustainability, 2022)
Realisation of the sustainable development goals (SDGs) will provide improvements to people's lives and longevity of the planet. The architectural, engineering and construction (AEC) sectors have a potentially huge role in aiding the delivery of many SDGs; however, there appears to be a lack of research into the engagement within this sector. The leading environmental management system (EMS), ISO 14001, can enable organisations in the AEC sectors to improve their business operations, whilst minimising their impacts on the environment and improving society. Therefore, the study sets out to use institutional theory to determine the usefulness of ISO 14001 as a tool within the AEC sector and to demonstrate how the organisational benefits could facilitate the delivery of the SDGs. A stepwise PRISMA review process facilitated the compiling of academic articles and professional reports ( n = 44), which enabled the creation of an inventory of the perceived benefits ( n = 85) and the recognised barriers ( n = 63) to implementing ISO 14001 across the AEC sectors. These barriers and benefits were confirmed by environmental practitioners as being relevant to the incorporation of an EMS. The most widely reported benefits within the AEC sectors were improving environmental performance and compliance with legislation. Lack of government pressure and lack of expertise were the most widely reported barriers, followed by cost to AEC organisations utilising an EMS. Following on from this inventory of benefits, it was possible to develop of a conceptual roadmap, which illustrates where linkages exist with the SDGs. SDG 4, 8, 12 and 13 are shown as exhibiting the most associations with the benefits. This roadmap was reviewed by AEC sector professionals who confirmed its usefulness. Therefore, it is surmised that the roadmap could aid strategic organisational sustainable planning or for organisations to demonstrate the delivery of their corporate social responsibilities.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Atmosphere surface storm track response to resolved ocean mesoscale in two sets of global climate model experiments - R. Justin Small; Rym Msadek; Young-Oh Kwon; James F. Booth; Colin Zarzycki (Climate Dynamics, 2019)

Stable isotope relationships between mothers, eggs and hatchlings in loggerhead sea turtles Caretta caretta - Alice S. Carpentier; David T. Booth; Karen E. Arthur; Colin J. Limpus (Marine Biology, 2015)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Characterisation and sediment–source linkages of intertidal sediment of the UK’s north Sefton Coast using magnetic and textural properties: findings and limitations - Vanessa J. C. Holden; Annie T. Worsley; Colin A. Booth; Graham Lymbery (Ocean Dynamics, 2011)

Magneto-biomonitoring of intra-urban spatial variations of particulate matter using tree leaves - Ann L. Power; Ann T. Worsley; Colin Booth (Environmental Geochemistry and Health, 2009)

Dear Readers - Colin Booth; Chris Wolkersdorfer; Bob Kleinmann (Mine Water and the Environment, 2007)

Dear Readers: - Colin Booth; Bob Kleinmann (Mine Water and the Environment, 2006)

Dear Readers: - Colin Booth; Bob Kleinmann (Mine Water and the Environment, 2006)

Dear Readers - Bob Kleinmann; Colin Booth (Mine Water and the Environment, 2006)

Dear Readers: - Bob Kleinmann; Colin Booth (Mine Water and the Environment, 2005)

Dear Readers: - Bob Kleinmann; Colin Booth (Mine Water and the Environment, 2005)

Dear Readers: - Bob Kleinmann; Colin Booth (Mine Water and the Environment, 2005)

Dear readers: - Bob Kleinmann; Colin Booth (Mine Water and the Environment, 2005)

A Note from the Editors - Bob Kleinmann; Colin Booth (Mine Water and the Environment, 2002)

Editors’ Note - Bob Kleinmann; Colin Booth (Mine Water and the Environment, 2002)

The biology of the panga, Pterogymnus laniarius (Teleostei: Sparidae), on the Agulhas Bank, South Africa - Anthony J. Booth; Colin D. Buxton (Environmental Biology of Fishes, 1997)